IMPLEMENTASI METODE PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA MADRASAH IBTIDAIYAH - Oktarina, Elsi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking is a crucial competency that needs to be fostered in *Madrasah Ibtidaiyah Islamic elementary school students to meet the challenges of 21st century learning. One approach considered effective for facilitating the development of this skill is Problem Based Learning (PBL), which places students at the center of the learning process through the resolution of contextual problems. This study aims to describe the implementation of the Problem-Based Learning method in enhancing the critical thinking skills of Madrasah Ibtidaiyah students. The study employed a qualitative approach with a case study design. The research subjects consisted of classroom teachers and Madrasah Ibtidaiyah students selected through purposive sampling. Data were collected via observation, in-depth interviews, and document analysis, and subsequently analyzed using an interactive analysis model comprising data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results indicate that the implementation of Problem Based Learning proceeded through stages involving problem orientation, student organization, investigation, result formulation and presentation, and reflection. This process encouraged students to be more active in identifying problems, analyzing information, expressing opinions based on evidence, collaborating in groups, and formulating solutions to the problems presented. Although challenges arose such as disparities in student abilities and limited instructional time teachers were able to overcome them through effective guidance and classroom management. Thus, the Problem Based Learning method contributes positively to developing the critical thinking skills of Madrasah Ibtidaiyah students through active, collaborative, and student centered learning.